Tokoh Bisma dalam Dramatari Amba Bisma - Mulyati, Eti; Rusliana, Iyus (Panggung, 2020)
ABSTRACT Dramatari Amba Bisma is one of the works of Iyus Ruslianan and Eti Mulyati from the results of research on the art that was performed at the Sunan Ambu Building, on October 28, 2019. The Dramatari was sourced from the Mahabharata and Bharatayuda plays, from the Mahabharata play that sparked the meeting of Amba and Bisma while still on October 28, 2019. girls and young men who differed in their desires and purpose in life, while from Bharatayuda’s story told about the death of Bhishma in the Bharatayuda war. This article aims to reveal the figure of Bhishma in Amba Bhishma’s drama, Bhishma is one of the characters in puppets who are magic and do not want to be crowned as kings for the Hastinapur family, he chose the way of life as a receipt rather than as a king. Because of his life choices, he was determined not to get married. Not only does Bhishma have a very problematic way of life, but many positive qualities deserve to be emulated. The method used is qualitative with a descriptive analysis approach, namely through literature study, interviews, and participatory observation. The results obtained from the analysis of Amba Bisma’s dramatari work can be seen by two positive characters in Bisma, namely; 1) sacrifices. 2) More loyal to the knight’s oath than to the family that is most dear. During the Baratayuda Bisma war as warlord on the Kurawa side, he was killed by Srikandi’s arrow. Keywords: Bhishma, Dramatari,Mahabharata,Bharatayuda ABSTRAK Dramatari Amba Bisma merupakan salah satu karya Iyus Ruslianan dan Eti Mulyati dari hasil penelitian karya seni yang di pertunjukan di Gedung Sunan Ambu, pada tanggal 28 Oktober 2019. Dramatari tersebut bersumber dari lakon Mahabharata dan Bharatayuda, dari lakon Mahabharata menceritkan pertemuan Amba dan Bisma saat masih gadis dan jejaka yang berbeda keingin dan tujuan hidupnya, sedangkan dari lakon Bharatayuda menceritakan tetang gugurnya Bisma dalam perang Bharatayuda. Artikel ini bertujuan ingin mengungkapkan tokoh Bisma dalam dramatari Amba Bisma, yakni Bisma merupakan salah satu tokoh dalam pewayangan yang merupakan tokoh sakti dan tidak bersedia dinobatkan sebagai raja demi kesatuan keluarga Hastinapura, Bisma memilih jalan hidup sebagai resi ketimbang sebagai raja. Hal ini diperkuat dengan keyakinannya, untuk tidak menikah. Bisma tidak hanya memiliki jalan hidup yang sangat problematik, akan tetapi banyak sifat positif yang pantas untuk diteladani. Metode yang digunakan adalah kualitatif dengan pendekatan deskriptif analisis, yaitu melalui studi pustaka, wawancara, dan observasi partisipasi. Hasil yang diperoleh dari analisis garapan dramatari Amba Bisma dapat diketahui dua karakter positif yang ada pada diri Bisma yaitu; 1) suka berkorban. 2) Lebih setia pada sumpah kesatria ketimbang dengan keluarga yang paling disayangi. Pada perang Baratayuda Bisma sebagai panglima perang di pihak Kurawa menemui ajalnya tertusuk panahnya Srikandi. Kata Kunci: Tokoh Bisma, dramatari, Mahabharata, Bharatayuda